2012
DOI: 10.1111/gcb.12033
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐diameter growth relationships of black spruce and jack pine trees in borealOntario,Canada

Abstract: To predict the long-term effects of climate change - global warming and changes in precipitation - on the diameter (radial) growth of jack pine (Pinus banksiana Lamb.) and black spruce (Picea mariana [Mill.] B.S.P.) trees in boreal Ontario, we modified an existing diameter growth model to include climate variables. Diameter chronologies of 927 jack pine and 1173 black spruce trees, growing in the area from 47°N to 50°N and 80°W to 92°W, were used to develop diameter growth models in a nonlinear mixed-effects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 53 publications
4
52
0
1
Order By: Relevance
“…Previous studies indicated that the relationship between mean annual precipitation and tree AGB or net primary productivity, on the most of sites, could be described by a nonlinear, concave-down function (Hsu et al 2012). The decline in the AGB was likely an indirect effect mediated by the availability of other resources (Hsu et al 2012;Subedi and Sharma 2013). While additional moisture usually increases tree biomass in dry-to-mesic ecosystems, increasing precipitation in humid ecosystems may reduce tree biomass by decreasing radiation, increasing nutrient leaching, or reducing soil oxygen availability (Schuur 2003;Hsu et al 2012).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies indicated that the relationship between mean annual precipitation and tree AGB or net primary productivity, on the most of sites, could be described by a nonlinear, concave-down function (Hsu et al 2012). The decline in the AGB was likely an indirect effect mediated by the availability of other resources (Hsu et al 2012;Subedi and Sharma 2013). While additional moisture usually increases tree biomass in dry-to-mesic ecosystems, increasing precipitation in humid ecosystems may reduce tree biomass by decreasing radiation, increasing nutrient leaching, or reducing soil oxygen availability (Schuur 2003;Hsu et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…While additional moisture usually increases tree biomass in dry-to-mesic ecosystems, increasing precipitation in humid ecosystems may reduce tree biomass by decreasing radiation, increasing nutrient leaching, or reducing soil oxygen availability (Schuur 2003;Hsu et al 2012). Increasing precipitation may also reduce the diffusion of oxygen through water-filled pores, as well as decomposition rates (Subedi and Sharma 2013). In addition, the results that an increase in precipitation led to the decrease of AGB could be also explained by biological traits of Masson pine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…以全球变暖和大气CO 2 浓度升高为主要特征的 全球变化正持续影响着陆地生态系统的结构和功 能, 威胁着人类的生存与健康, 因而备受世界各国 政府和科学家的普遍关注 (Oreskes, 2004;Bellard et al, 2012;Eklöf et al, 2012)。 大量的监测和模型模拟 研究表明, 20世纪开始的全球温室效应不断继续着, 而且有不断扩大的趋势(IPCC, 2007)。 全球平均地表 温度在20世纪已经增加了大约0.6 K (Houghton et al, 2001), 并且在未来几十年可能还会快速地上升 (Zwiers, 2002)。研究表明, 冬春季节增温可显著改 变植物物候 (Morin et al, 2010;Yu et al, 2010;Fu et al, 2015;Wheeler et al, 2015)、生长和功能特征 (Dorji et al, 2013;Subedi & Sharma, 2013)、开花和 繁殖 (Cook et al, 2012)、生理生态 (Fan et al, 2015), et al, 2008), 因此被认为是生物界中普遍存在的一 种规律 (West et al, 1999;Niklas & Enquist, 2002 …”
unclassified